2013
DOI: 10.1108/ijph-03-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Shakespeare in Prison: affecting health and wellbeing

Abstract: To the best of our knowledge this is the first research of its kind and provides valuable insights into the role that theatre may play in fostering social support in the prison context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Policymakers have explored a variety of approaches to achieve these goals, including more conventional programs such as mental health therapy and addictions treatment as well as alternative programs ranging from meditation retreats to Shakespearean theater (Council of State Governments Justice Center, 2014; Heard et al, 2013;Perelman et al, 2012). One promising but understudied approach is the implementation of prison-based dog programs (PDPs), in which inmates become dog handlers who train the animals for adoption or service work (Van Wormer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Policymakers have explored a variety of approaches to achieve these goals, including more conventional programs such as mental health therapy and addictions treatment as well as alternative programs ranging from meditation retreats to Shakespearean theater (Council of State Governments Justice Center, 2014; Heard et al, 2013;Perelman et al, 2012). One promising but understudied approach is the implementation of prison-based dog programs (PDPs), in which inmates become dog handlers who train the animals for adoption or service work (Van Wormer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, U.S. and European correctional services have proposed various efforts to combat the high levels of stress and anger in prison (Bouw et al, 2019), and heighten inmates’ awareness of the potential consequences of these and other negative emotions (Hughes & Wilson, 2018). Such measures include physical exercise (Battaglia et al, 2015; O’Toole et al, 2018; Woods et al, 2017), recreational activities (Basaran, 2016; Edgemon & Clay-Warner, 2018), and formal and informal educational programs (Flynn et al, 2020; Heard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this growing evidence base in support of arts engagement and health gains in non-clinical settings, there is a dearth of research on the mental health impact of arts engagement among men, particularly men of low socioeconomic status (SES). A small number of studies reported improved mental well-being, social relationships, a sense of achievement, routine and structure among men following arts engagement ( Thomas et al ., 2011 ; Heard et al ., 2013 ; Wilkinson and Caulfield, 2017 ). However, these studies did not set out to explicitly recruit men or explore men’s experiences of the arts and were not underpinned by social constructionist theories of masculinities.…”
Section: Introductionmentioning
confidence: 99%